Phytochemical, Antioxidant and Mitochondrial Permeability Transition Studies on Fruit-Skin Ethanol Extract of Annona muricata - Wisdom O. Iyanda-Joel; Olusayo B. Ajetunmobi; Shalom N. Chinedu; Emeka E. J. Iweala; Oluwatobi S. Adegbite (Journal of Toxicology)
Uncontrolled cell proliferation hallmarks cancer and most cancer cells have developed multiple resistance to the drugs employed for their treatment. The study examined the phytochemical and antioxidant properties of the fruit-skin ethanol extract of Annona muricata Linn. (ESA) and its effect on rat liver mitochondrial membrane permeability transition (MMPT). Qualitative phytochemical study and antioxidant assays were carried out following established protocols while the opening of the MMPT pore in the presence of varying concentrations of the extract was assayed spectrophotometrically under succinate-energized conditions. Calcium chloride (CaCl2) and spermine were used to trigger and inhibit pore opening respectively. Cytochrome c release was assayed for using ELISA kit. Terpenoids, steroids, phenols among other phytochemicals were found present in ESA and the extract showed very low antioxidant properties at the tested concentrations based on the diphenyl-1-picryhydrazyl (DPPH) radical scavenging activity assay. Lipid peroxidation was induced in a concentration-dependent manner on both the cytosolic and mitochondrial hepatocyte fractions in vitro. In the absence of CaCl2 0.84 mg/mL concentration of ESA induced MMPT pore opening by 129% while the extracts showed no inhibitory activity in its presence. The induction fold corresponded with the concentrations of cytochrome c released. The fruit-skin ethanol extract of Annona muricata at certain concentrations may possibly contain bioactive compounds that induce apoptosis.